Ag(I)-mediated homo and hetero pairs of guanosine and cytidine: monitoring by circular dichroism spectroscopy - Goncharova, Iryna (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2014)
Ag(I)-containing compounds are attractive as antibacterial and antifungal agents. The renewed interest in the application of silver(I) compounds has led to the need for detailed knowledge of the mechanism of their action. One of the possible ways is the coordination of Ag(I) to G-C pairs of DNA, where Ag(+) ions form Ag(I)-mediated base pairs and inhibit the transcription. Herein, a systematic chiroptical study on silver(I)-mediated homo and mixed pairs of the C-G complementary-base derivatives cytidine(C) and 5'-guanosine monophosphate(G) in water is presented. Ag(I)-mediated homo and hetero pairs of G and C and their self-assembled species were studied under two pH levels (7.0 and 10.0) by vibrational (VCD) and electronic circular dichroism(ECD). VCD was used for the first time in this field and showed itself to be a powerful method for obtaining specific structural information in solution. Based on results of the VCD experiments, the different geometries of the homo pairs were proposed under pH 7.0 and 10.0. ECD was used as a diagnostic tool to characterize the studied systems and as a contact point between the previously defined structures of the metal or proton mediated pairs of nucleobases and the systems studied here. On the basis of the obtained data, the formation of the self-assembled species of cytidine with a structure similar to the i-motif structure in DNA was proposed at pH 10.0.
Keywords: guanosin; párování bází; Protons; Ag(I)-mediated pair; Spectrophotometry, Ultraviolet; Circular Dichroism; G–C pair; Base Pairing; protony; Silver; Guanosine; vibrace; Cytidine; cirkulární dichroismus; Spectrophotometry, Infrared; VCD infrared spectroscopy; ECD; stříbro; Vibration; spektrofotometrie ultrafialová; spektrofotometrie infračervená; cytidin